2012
DOI: 10.1183/09031936.00030412
|View full text |Cite
|
Sign up to set email alerts
|

Hestia criteria can discriminate high- from low-risk patients with pulmonary embolism

Abstract: We investigated whether the clinical criteria used in the Hestia study for selection of pulmonary embolism (PE) patients for outpatient treatment could discriminate PE patients with high and low risk for adverse clinical outcome.We performed a cohort study with PE patients who were triaged with 11 criteria for outpatient treatment. Patients not eligible for outpatient treatment were treated in hospital. Study outcomes were recurrent venous thromboembolism, major bleeding and all-cause mortality during 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 13 publications
1
34
1
3
Order By: Relevance
“…Patients in our study have demonstrably lower hospital charges and have been previously shown to have improved outcomes over similar patients who are hospitalized. 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in our study have demonstrably lower hospital charges and have been previously shown to have improved outcomes over similar patients who are hospitalized. 5 …”
Section: Discussionmentioning
confidence: 99%
“…While DVT has been treated as an outpatient for many years, recently developed risk stratification tools have been validated to select patients with PE who have a low risk of shortterm complications. [1][2][3][4][5][6][7] In particular, the Hestia criteria identifies a subgroup of PE patients who have a 1.0% mortality rate as outpatients over 3 months and a low rate of short-term complications requiring rehospitalization. 8 In this article, we assumed that many patients with DVT have undiagnosed PE and therefore must undergo the same risk stratification as patients with documented PE.…”
mentioning
confidence: 99%
“…Despite many prognostic model have been proposed, such as the ESC prognostic model, the original and sPESI score, the Geneva prognostic model, the LR-PED, the HESTIA criteria, the Spanish score and other, which is the best prognosticator for the identification of 30-days mortality in PE patients in real world remains unclear. 4,5,9,10,[17][18][19][20] Moreover, the majority of the proposed prognostic models focus only on early mortality risk without bleeding risk stratification. On the other hand, few bleeding risk scores have been proposed, but, anyway, these do not give information about PE-related early mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the treatment of PE at home has been formally assessed 20 . Nowadays, we have been provided with a validated tool (the Hestia Criteria, Table 3) that safely identifies patients who do not need to be admitted for the management of PE 21 . Patients with extensive iliofemoral DVT or phlegmasia cerulea dolens, which are conditions that carry a high risk of severe post-thrombotic syndrome or those that require parenteral or opioid analgesia, were usually excluded from RCT, although they should been included.…”
Section: Burden Of Venous Thromboembolismmentioning
confidence: 99%